Raw Material Planning and Control with MRP Method to Maintain Accurate Production Amounts in UKM Allwooden Woodworking - Mochammad Rofieq; Jihan Maudy Faradhisa; Primahasmi Dalulia (Tibuana, 2022)
Allwooden Woodworking is a Micro and Small Enterprise (MSE) which is entrepreneurship in the production of furniture, such as tables, chairs, and cupboards. These MSE focus on the selection of good and quality raw materials. This study aims to find out when raw materials in MSE can be available at the right time with the amount according to the demand of suppliers. The method used in this research is Material Requirement Planning (MRP). The results obtained from this study are in the form of planning and controlling raw materials that contain scheduling material purchases and product manufacture regularly and determining the size of an economical order of raw materials to avoid product overstock.